Letter - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960
1943-10-11 038-0016-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND BASQUE CHILDREN'S TRUST LTD. PRESIDENT: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. CHAIRMAN: MISS ELEANOR RATHBONE, M.P. VICE-CHAIRMAN: THE EARL OF LISTOWEL. HON. SECRETARIES: LADY LAYTON Mr. D.R. GRENFELL, M.P. Mr. WILFRID ROBERTS, M.P. HON. APPEALS SECRETARY: Mrs. V.E. MILLER SECRETARY: MISS M. PICKEN. 39, VICTORIA STREET, LONDON, S.W.1. TELEPHONE: ABBEY 7463 11th October, 1943. Dear Miss Adam, When hundreds of little Basque refugees were first given sanctuary in this country in 1936, sympathy was quickly aroused for these pathetic little orphans of War, who, after terrifying months of danger and privation, found themselves in a strange country which must have seemed drab and cold indeed after the warm Spanish sunshine. Few spare a thought for these little visitors to-day when so many other necessitous and deserving causes are appealing urgently for help! But we cannot go back on our responsibilities. The War has made it necessary to provide for these children for a much longer period than we had ever visualised. Our repatriation scheme has had to be deferred and, meanwhile, help we were receiving from America has inevitably been reduced since her entry into the War. True, the relaxation of Regulations in regard to alien labour has relieved us of providing for adult refugees and some of the older children who can now find employment. It is necessary, however, to give advice and help in every-day problems in all cases. There are still three hostels open and 400 Basque 292/946/38/16(I)